Morphological and molecular characteristics of the species Cosmocerca commutata and C. ornata (Nematoda: Cosmocercidae) in Uzbekistan - E.E. IKROMOV; A.E. KUCHBOEV; E.F. IKROMOV; N. SÜMER; H.S. YILDIRIMHAN; O.O. AMIROV; B. ZHUMABEKOVA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Ikromov EE, Kuchboev AE, Ikromov EF, Sümer N, Yildirimhan HS, Amirov OO, Zhumabekova B. 2023. Morphological and molecular characteristics of the species Cosmocerca commutata and C. ornata (Nematoda: Cosmocercidae) in Uzbekistan. Biodiversitas 24: 4609-4616. In studies on the helminth fauna of amphibians conducted by numerous researchers, two species of the genus Cosmocerca, namely Cosmocerca ornata (Dujardin, 1845) Diesing, 1861 and C. commutata (Diesing, 1851), have emerged as the most common and extensively studied. This paper elucidates the morphology and molecular characteristics of two nematode species, Cosmocerca commutata and C. ornata, found in the intestines of Pelophylax sp. and Bufotes pewzowi in the Ferghana Valley of Uzbekistan. The captured amphibians were individually kept in plastic bags with water and vegetation until the examination. It is the first record of B. pewzowi as a host for both species C. commutata and C. ornata. Standard methods were used for the fixation and processing of nematodes. These nematodes ?orphologically differ in body size, relative length of spicules and gubernaculum (C. commutata has twice the length of gubernaculum and spicules compared to C. ornata), shape and number of plectanes (C. commutata has 8 pairs of plectans and 4 pairs of caudal papillae, while C. ornata has 5 pairs of plectanes and 3 pairs of caudal papillae), and tail morphology and length. The morphological evidence supports that C. commutata and C. ornata commonly parasitize anurans in Uzbekistan. This study provides molecular data of both species and their sequences differed by 1.5% (6 bp) in the ITS1+5.8S+ITS2 region. Each species of them formed a well-supported clade in the phylogenetic tree. Our findings contribute to the comprehension of species and genetic diversity of the genus Cosmocerca in Uzbekistan.